Countering right wing extremism in education: schooling in the racist badland - Mattsson, Christer (Routledge studies in countering violent extremism, 2025)
"This book investigates how schools deal with racism and extremism, focusing on everyday life, students, and the surrounding community and geographical area. There is a lack of clarity on how racism and extremism should be managed in schools. Through extensive ethnographical data, interviews and focus group interviews with students and school staff in mill towns and racist strongholds in Sweden, this book focuses on how racism and right-wing extremism are enacted, played out, and dealt with. It draws on theories of everyday and institutional racism as well as institutional ethnography. Formal and informal school strategies and pedagogical interventions intended to manage recurring problems in schools are discussed. The text offers a deeper insight into how racism and right-wing/neo-Nazism extremism are enacted and confronted in a rural Swedish school context and beyond. This book will be of interest to students of Terrorism Studies, Sociology, Cultural Studies, and Security Studies"--